Methionine Restriction Improves Gut Barrier Function by Reshaping Diurnal Rhythms of Inflammation-Related Microbes in Aged Mice - Ren, Bo; Wang, Luanfeng; Mulati, Aiziguli; Liu, Yan; Liu, Zhigang; Liu, Xuebo (Frontiers in Nutrition, 2021)
Age-related gut barrier dysfunction and dysbiosis of the gut microbiome play crucial roles in human aging. Dietary methionine restriction (MR) has been reported to extend lifespan and reduce the inflammatory response; however, its protective effects on age-related gut barrier dysfunction remain unclear. Accordingly, we focus on the effects of MR on inflammation and gut function. We found a 3-month methionine-restriction reduced inflammatory factors in the serum of aged mice. Moreover, MR reduced gut permeability in aged mice and increased the levels of the tight junction proteins mRNAs, including those of occludin, claudin-1, and zona occludens-1. MR significantly reduced bacterial endotoxin lipopolysaccharide concentration in aged mice serum. By using 16s rRNA sequencing to analyze microbiome diurnal rhythmicity during 24 hours, we found MR moderately recovered the cyclical fluctuations disruption of aged mice, leading to time-specific enhancement of the abundance of short-chain fatty acid-producing and lifespan-promoting microbes. Moreover, MR dampened the oscillation of inflammation-related TM7-3 and Staphylococcaceae. In conclusion, the effects of MR on the gut barrier were likely related to alleviation of the oscillations of inflammation-related microbes. MR can enable nutritional intervention against age-related gut barrier dysfunction.